Optimalisasi Soft Skills Guru melalui Projek Penguatan Profil Pelajar Pancasila Berbasis Literasi Sains - Awalina Barokah; Titin Sunaryati; Yossi Srianita; Dinda Tri Oktavia (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to optimize the strengthening of teachers' soft skills through the implementation of the Pancasila Student Profile Strengthening Project (P5) based on scientific literacy. Soft skills such as communication, collaboration, critical thinking, and leadership are essential competencies for teachers in creating meaningful and transformative learning. This activity was carried out in several public elementary schools in Bekasi City with a participatory training approach and direct practice-based mentoring. The training materials were designed to integrate scientific literacy with Pancasila values ​​in the context of thematic learning. The results of the activity showed a significant increase in communication skills, collaboration skills, and teacher understanding in applying the dimensions of the Pancasila Student Profile into the learning process. In addition, this program also had a positive impact on shaping the professional behavior of teachers who were more reflective, collaborative, and oriented towards strengthening student character. These findings indicate that the integration of scientific literacy within the P5 framework can be an effective strategy in developing teachers' pedagogical competence.